Social support and its relationship to psychological resilience for students with visual impairment - Al-qassabi, Khalifa Ahmed; Al-bimani, Muna Hammad (Journal of Educational and Psychological Sciences, 2021)
The research aimed to identify the extent of social support contributes to the psychological flexibility among students with visual impairment at Omar bin Al Khattab Institute for Blind. The research sample consists of (120) male and female students. The research used the relational descriptive method. Two scales were used: the Psychological Resilience Scale for Al-Salahi (2017), and the Hamri and Medani Social Support Scale (2016). The study showed that the sample is having medium of psychological flexibility with different dimensions. The results also showed a lack of statistically significant differences between males and females in the average of psychological flexibility. The results indicated that there is a statistically significant positive relationship between psychological flexibility and social support, and that both dimensions of support provided by blind and non-blind friends contribute significantly to predicting the increase in psychological flexibility in the study sample. The study recommended to increase and improve the level of formal and informal social services for the visual impairment category in the Sultanate of Oman and conduct more studies and researches on physiological flexibility in the light of physiological and social variables with visual impairment category.
Keywords: psychological flexibility; social support; visual impairment students